PENGUASAAN KONSEP MATEMATIKA SISWA SMP DITINJAU DARI KEYAKINAN EPISTEMOLOGIS TENTANG MATEMATIKA DAN KECERDASAN EMOSIONAL - shentia liyuwana defi; I Nengah Parta; Hendro Permadi (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
This study aims to investigate the relationship between students' mathematical beliefs and levels of emotional intelligence with mastery of mathematical concepts. This type of research is a correlational study because it aims to determine the relationship between variable  (epistemological beliefs about mathematics) and variable  (emotional intelligence) with variable Y (mastery of mathematical concepts). The population in this study were students of SMP Islam Darussholihin Campurdarat, Tulungagung. The sample in this study was class VII with a total of 42 students. The instruments in this study were a questionnaire on mathematical beliefs and emotional intelligence as well as a test of mastery of the mathematical concept of the quadrilateral material. The technique of processing and analyzing data in this study uses the correlation test. The results of correlation testing in this study indicate that: (1) There is a significant relationship between epistemological beliefs about mathematics on students' mastery of mathematical concepts with a correlation coefficient value of  which means the correlation is classified as strong, (2) There is a significant relationship between emotional intelligence and mastery of mathematical concepts with a correlation coefficient of 0.449, which means the correlation is moderate, and (3) There is a significant relationship between epistemological beliefs about mathematics and emotional intelligence simultaneously on students' mastery of mathematical concepts with a correlation coefficient value of 0.573 which means the correlation is strong.